Maximum Likelihood Estimation of the Fractional Differencing Parameter in an Arfima Model Using Wavelets - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2002)
In this paper, we examine the finite-sample properties of the approximate maximum likelihood estimate (MLE) of the fractional differencing parameter d in an ARFIMA(p, d, q) model based on the wavelet coefficients. Ignoring wavelet coefficients of higher order of resolution, the remaining wavelet coefficients approximate a sample of independently and identically distributed normal variates with homogeneous variance within each level. The approximate MLE performs satisfactorily and provides a robust estimate for which the short memory component need not be specified.